The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/children9091372
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Multi-Systemic Complications of a Ketogenic Diet in Children and Infants with Epilepsy

Abstract: Ketogenic diets (KDs) are highly effective in the treatment of epilepsy. However, numerous complications have been reported. During the initiation phase of the diet, common side effects include vomiting, hypoglycemia, metabolic acidosis and refusal of the diet. While on the diet, the side effects involve the following systems: gastrointestinal, hepatic, cardiovascular, renal, dermatological, hematologic and bone. Many of the common side effects can be tackled easily with careful monitoring including blood coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 138 publications
1
11
0
Order By: Relevance
“…Furthermore, the high fat content of the diet may have negative impacts on physical growth and development, and there are also concerns about an increased risk of future metabolic disease. 6,15 For this reason, intermittent KD or switching between dietary regimens has been proposed as a solution. 8 Results of the present study demonstrate that the benefits of the KD on seizure frequency are quickly reversed following 72 h of carbohydrate exposure in a model of ISS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the high fat content of the diet may have negative impacts on physical growth and development, and there are also concerns about an increased risk of future metabolic disease. 6,15 For this reason, intermittent KD or switching between dietary regimens has been proposed as a solution. 8 Results of the present study demonstrate that the benefits of the KD on seizure frequency are quickly reversed following 72 h of carbohydrate exposure in a model of ISS.…”
Section: Discussionmentioning
confidence: 99%
“…Although therapeutically beneficial, the strict dietary requirements of KD adherence can be challenging. Furthermore, the high fat content of the diet may have negative impacts on physical growth and development, and there are also concerns about an increased risk of future metabolic disease 6,15 . For this reason, intermittent KD or switching between dietary regimens has been proposed as a solution 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Concerns regarding PB are that the acidosis produced by the diet may create a favorable environment to allow PB to enter the brain producing drowsiness and even encephalopathy in some cases 38 . Therefore, some authors recommend avoiding or reducing the dose of PB and to monitor PB plasma levels in patients on KDT 39 . Additionally, intravenous PB (and pentobarbital) has a high propylene glycol content, which is a carbohydrate and hence may reduce ketosis 40 …”
Section: Methodsmentioning
confidence: 99%
“…38 Therefore, some authors recommend avoiding or reducing the dose of PB and to monitor PB plasma levels in patients on KDT. 39 Additionally, intravenous PB (and pentobarbital) has a high propylene glycol content, which is a carbohydrate and hence may reduce ketosis. 40 In the previously mentioned study by Morrison et al, 32 it was found that children who received PB in combination with the KDT were less likely to have a >50% seizure reduction at 3 months than those receiving the KDT in combination with the other five ASMs examined in the study (VPA, TPM, LEV, LTG, and ZNS).…”
Section: Phenobarbitalmentioning
confidence: 99%
“…Although the classical KD has been used in epilepsy for many years and its efficacy in reducing seizures has been confirmed in several studies, especially when introduced in young age, 35 the mechanism behind the effects is not well understood in humans. In particular, it is not known why this dietary intervention has an anti‐seizure effect in a proportion of the patients, while in others there is poor or no effect 35 or even worsening of seizure frequency or appearance of adverse effects 42‐44 . Perna and colleagues 45 showed that out of 24 patients with DRE, almost 60% benefited from the KD intervention, with a >50% reduction in seizure frequency in the first 3 months of treatment.…”
Section: Ketogenic Diets In the Management Of Drementioning
confidence: 99%